2017
DOI: 10.1007/s00428-017-2257-1
|View full text |Cite
|
Sign up to set email alerts
|

Size and heterologous elements predict metastases in malignant phyllodes tumours of the breast

Abstract: Phyllodes tumours (PTs) of the breast are uncommon fibroepithelial neoplasms comprising 0.3-1.0% of all primary breast tumours. The majority of PTs are benign and generally well managed with surgery. However, malignant PTs, and occasionally borderline PTs, can behave in a clinically aggressive manner by metastasizing to distant organs. Although distant metastasis is rare, the prognosis of patients with metastasis is dismal as many are unresponsive to standard chemotherapy and the risk of death is high. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Koh et al recently reported a series of 83 cases of malignant PT showing that large tumours (≥90 mm) containing malignant heterologous elements disclosed significantly worse metastasis-free survival and a trend for poorer overall survival. 26 Multivariate analysis confirmed marked cytological atypia as an independent prognostic factor for cumulative incidence of phyllodes-related recurrence.…”
Section: Discussionmentioning
confidence: 82%
“…Koh et al recently reported a series of 83 cases of malignant PT showing that large tumours (≥90 mm) containing malignant heterologous elements disclosed significantly worse metastasis-free survival and a trend for poorer overall survival. 26 Multivariate analysis confirmed marked cytological atypia as an independent prognostic factor for cumulative incidence of phyllodes-related recurrence.…”
Section: Discussionmentioning
confidence: 82%
“…In this case, she was diagnosed of distant metastasis to stomach after the symptoms of frequent melena and drop of hemoglobin level. However, she had anemia in the beginnings (hemoglobin level was in the range of 8 10 mg/dL) before total mastectomy. CT of chest- abdomen showed no overt evidence of distant metastasis while intraluminal lesions of gastrointestinal tract might be unclear in CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…The median size of PTs is about 4 cm. Those size larger than 10 cm are less than 10% of PTs, and the largest one so far is up to 50 × 50 cm reported by Islam et al [ 4 , 5 ] Approximately 10–15% of PTs are malignant, and only 10–26% of malignant PTs are found with metastasis [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benign PTs are reported to recur locally at a rate of 10–17%, while the recurrent likelihood is higher for borderline and malignant PTs, at 14–25% and 23–30%, respectively . Malignant PTs also have an increased potential to metastasise to distant sites such as the lungs, bone, brain, and liver, leading to a poor prognosis and a higher risk of death as there is limited success of radiotherapy and chemotherapy .…”
Section: Introductionmentioning
confidence: 99%